A Novel Classification of the Inframammary Fold for Use in Primary Breast Augmentation. Issue 6 (13th October 2021) - Phillips, Nicole A.; Millan, Lincoln S.; Miroshnik, Michael; Stradwick, Luke; Layt, Craig
Abstract : Background: Previous aesthetic breast surgery algorithms have not addressed the importance of evaluating the native inframammary fold before primary breast augmentation. In the authors' experience, assessment of native inframammary fold anatomy significantly impacts surgical planning and technique. Failure to adequately evaluate and manage the inframammary fold leads to many of the common problems of the lower pole, including double-bubble deformity. Methods: The authors assessed the inframammary fold preoperatively in 2192 consecutive patients undergoing primary breast augmentation between June of 2014 and December of 2018. A novel classification of inframammary fold morphology was devised based on review of standardized preoperative photographs. Outcome assessment was performed postoperatively at 3-month intervals. Results: The authors identified four clear inframammary fold subtypes based on their clinical appearance, ranging from the nonexistent type F0 to the well-formed and fixed type F3. The key outcome measure examined was the presence of double-bubble deformity postoperatively. There were three total cases of double-bubble deformity identified in our cohort (<1 percent of patients). All cases of double-bubble deformity occurred in patients with a type 3 fold. Conclusions: The inframammary fold defines the inferior boundary of the lower pole of the breast and is a critical landmark to the aesthetic breast surgeon. The authors describe a unique and simple inframammary fold classification system that assists in selection of the appropriate approach to the inframammary fold in addition to implant dimensional planning. The authors have found that this system—in particular, the identification of the type F3 inframammary fold—has minimized the risk of inframammary fold–associated complications in over 2000 cases. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.